Degenerate mapping of environmental location presages deficits in object-location encoding and memory in the 5xFAD mouse model for Alzheimer's disease - Hai Zhang; Lujia Chen; Kevin G. Johnston; Joshua Crapser; Kim N. Green; Nicole My-Linh Ha; Andrea J. Tenner; Todd C. Holmes; Douglas A. Nitz; Xiangmin Xu (Neurobiology of Disease, 2023)
A key challenge in developing diagnosis and treatments for Alzheimer's disease (AD) is to detect abnormal network activity at as early a stage as possible. To date, behavioral and neurophysiological investigations in AD model mice have yet to conduct a longitudinal assessment of cellular pathology, memory deficits, and neurophysiological correlates of neuronal activity. We therefore examined the temporal relationships between pathology, neuronal activities and spatial representation of environments, as well as object location memory deficits across multiple stages of development in the 5xFAD mice model and compared these results to those observed in wild-type mice. We performed longitudinal in vivo calcium imaging with miniscope on hippocampal CA1 neurons in behaving mice. We find that 5xFAD mice show amyloid plaque accumulation, depressed neuronal calcium activity during immobile states, and degenerate and unreliable hippocampal neuron spatial tuning to environmental location at early stages by 4 months of age while their object location memory (OLM) is comparable to WT mice. By 8 months of age, 5xFAD mice show deficits of OLM, which are accompanied by progressive degradation of spatial encoding and, eventually, impaired CA1 neural tuning to object-location pairings. Furthermore, depressed neuronal activity and unreliable spatial encoding at early stage are correlated with impaired performance in OLM at 8-month-old. Our results indicate the close connection between impaired hippocampal tuning to object-location and the presence of OLM deficits. The results also highlight that depressed baseline firing rates in hippocampal neurons during immobile states and unreliable spatial representation precede object memory deficits and predict memory deficits at older age, suggesting potential early opportunities for AD detecting.